2019
DOI: 10.3390/nu11102274
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of An Anthocyanin-Rich Antioxidant Juice Accelerates Recovery of Running Economy and Indirect Markers of Exercise-Induced Muscle Damage Following Downhill Running

Abstract: This study examined the effects of anthocyanin-rich antioxidant juice (AJ) on the recovery of exercise-induced muscle damage (EIMD) and the running economy (RE) following downhill running (DHR). Thirty healthy young men were randomly divided into two blinded groups and consumed either AJ or placebo (PLA) for nine days (240 mL twice-a-day). On day 5, the participants from both groups ran downhill (−15%) for 30 min at 70% of their maximal oxygen uptake (VO2max) speeds. The changes in RE (oxygen uptake (VO2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
(50 reference statements)
0
17
0
1
Order By: Relevance
“… a Decrease (% from baseline) in isometric maximal voluntary contraction (MVC) torque of knee extensors after downhill running (DR); b increase (% from baseline) in blood (plasma and serum) creatine kinase (CK) concentration after DR; c delayed onset muscle soreness (DOMS) response (0–100 mm evaluated on visual analogue scale) for knee extensors after DR. Based on data from original research articles reporting isometric MVC force/torque decrements ( n = 37; [ 5 , 9 , 10 , 15 , 38 , 43 , 58 87 ]), blood CK elevation ( n = 83; [ 14 , 16 , 38 , 40 42 , 44 , 46 , 50 , 59 62 , 65 67 , 70 , 72 75 , 77 , 80 , 81 , 84 , 85 , 87 90 , 92 , 121 , 134 183 ]) and DOMS ( n = 23; [ 8 , 15 , 38 , 58 , 60 , 66 , 71 , 75 , 84 , 89 , 135 , 151 , 156 , 159 , 171 , 178 , 179 , 182 , 184 188 ]) responses immediately post-, 24 h post-, 48 h post-, 72 h post- and 96 h ...…”
Section: Muscular Alterations Following Downhill Runningmentioning
confidence: 99%
See 1 more Smart Citation
“… a Decrease (% from baseline) in isometric maximal voluntary contraction (MVC) torque of knee extensors after downhill running (DR); b increase (% from baseline) in blood (plasma and serum) creatine kinase (CK) concentration after DR; c delayed onset muscle soreness (DOMS) response (0–100 mm evaluated on visual analogue scale) for knee extensors after DR. Based on data from original research articles reporting isometric MVC force/torque decrements ( n = 37; [ 5 , 9 , 10 , 15 , 38 , 43 , 58 87 ]), blood CK elevation ( n = 83; [ 14 , 16 , 38 , 40 42 , 44 , 46 , 50 , 59 62 , 65 67 , 70 , 72 75 , 77 , 80 , 81 , 84 , 85 , 87 90 , 92 , 121 , 134 183 ]) and DOMS ( n = 23; [ 8 , 15 , 38 , 58 , 60 , 66 , 71 , 75 , 84 , 89 , 135 , 151 , 156 , 159 , 171 , 178 , 179 , 182 , 184 188 ]) responses immediately post-, 24 h post-, 48 h post-, 72 h post- and 96 h ...…”
Section: Muscular Alterations Following Downhill Runningmentioning
confidence: 99%
“…, 44, 46, 50, 59-62, 65-67, 70, 72-75, 77, 80, 81, 84, 85, 87-90, 92, 121, 134-183] and DOMS[8,15,38,58,60,66,71,75,84,89,135,151,156,159,171,178,179,182,[184][185][186][187][188] peak from 24 to 48 h post-DR. Immediately post DR, a greater reduction in isometric MVC force/torque is observed in untrained (mean: − 23.5%; 95% CI: [− 26.9% to − 17.2%] compared to trained populations (− 16.4%; 95% CI: [ − 19.5% to -12.3%]).…”
mentioning
confidence: 99%
“…Other meta-analyses have not suggested an effect of fruit or (poly)phenols on CK (Doma et al 2021;Hill et al 2021), it should be acknowledged there are several criticisms of CK as a marker for muscle damage especially owing to its high inter and intra-individual variability and its meaningfulness as a recovery index (Brancaccio, Maffulli, and Limongelli 2007;Hill et al 2021;Warren, Lowe, and Armstrong 1999). However, some included studies in the current review found a benefit of ACN-rich foods (Carvalho et al 2018;(Lyall et al 2009) and an ACN rich cocktail on exercise-induced CK (Lima et al 2019) it therefore might be that some (poly)phenols such as ACN are more beneficial than others. Moreover, the large number of pooled studies at 48 hours post exercise might account for some of the variability, where the participant numbers amounted to 244.…”
Section: Discussionmentioning
confidence: 70%
“…Our study cannot find evidence of BC supplementation enhancing high-intensity exercise capacity and performance or enhancing the underlying physiologic parameters that govern high-intensity exercise, but nor do we find evidence of any detrimental effects. Thus, we cannot warrant the use of BC supplementation as an ergogenic aid, but we acknowledge that some, 8,10,11,17,[21][22][23][24][25][26][27] but not all 24,28,29 studies have indicated a positive ergogenic effect. Reasons for this discrepancy remain unknown, but it is possible that administration of BC supplementation must be concurrent to a high training load before a benefit may be realized, given that BC supplementation in some studies has facilitated recovery between exercise sessions, [25][26][27] possibly linked to enhanced Lahandling with reduced production and/or increased clearance 24 and tolerance, 22 reduced oxidative stress and inflammatory immune reactions, [2][3][4]8,9,39 and reduced muscle damage 17 following high-intensity exercise.…”
Section: Discussionmentioning
confidence: 94%
“…[3][4][5][6][7]12 Secondly, they reduce inflammations, 9 and thirdly, they help manage metabolic problems and overweight. 10,11 Further studies have indicated that BC and anthocyanin supplementation also may confer broad-spectrum positive acid/base effects, 13 anti-bacterial and anti-viral effects, 14,15 certain regenerative effects, 16 while also reducing exercise-induced cell and tissue damage, 8,9,17 tumor development and proliferation 18 as well as pain, fatigue and morbidity. 19,20 However, it is not always clear whether the observed action was caused by anthocyanins and their conjugates, other anthocyanin-derived metabolites, or other compounds or derivatives from the anthocyanin source.…”
Section: Introductionmentioning
confidence: 99%